Effect of air combustion preheater on furnace efficiency by using refinery simulator - Almosawi, Yosif J. Kadhem; Alshimmary, Warqaa A. Kadhem (Journal of Petroleum Research and Studies, 2017)
One of the basic crude oil refining steps is the heat up to high temperature about 3700 C, which is done in the furnace. The balance between fuel and air required to combustion provide an economical and efficient heating. In this research operating data of heating up the furnace are collected by using an interactive simulator of Drilling System Company (ORTIS) which gives a flexibility of operation cannot be obtained in real furnace, these data are related to find the operation paths under different control system of manual, automatic and working automatic without pre-heating are used . Using of combustion air preheater, by exchanging heat with the flue gases, leading to increase furnace heating efficiency from 85% to 93% also the fuel supplied to the burners is more less than working without preheater. As the simulator used in this research very closed to real operating system of furnace which cover all the variables of furnace inside temperatures, excess air analyzer, and fuel gas control and inside pressure control. The using of interactive simulator is very useful in stating the right operating conditions. The use of pre-heating of combustion air is best economical method to reach heating the crude oil to the required temperature with minimum fuel gas consumption, which directly affects the efficiencies of the furnace in each case.